Production of tailored hydroxylated prodiginine showing combinatorial activity with rhamnolipids against plant-parasitic nematodes - Kossmann, D. F.; Huang, M.; Weihmann, R.; Xiao, X.; Gätgens, F.; Weber, T. M.; Brass, H. U. C.; Bitzenhofer, N. L.; Ibrahim, S.; Bangert, K.; Rehling, L.; Mueller, C.; et al. (Frontiers in Microbiology, 2023)
Bacterial secondary metabolites exhibit diverse remarkable bioactivities and are thus the subject of study for different applications. Recently, the individual effectiveness of tripyrrolic prodiginines and rhamnolipids against the plant-parasitic nematode Heterodera schachtii, which causes tremendous losses in crop plants, was described. Notably, rhamnolipid production in engineered Pseudomonas putida strains has already reached industrial implementation. However, the non-natural hydroxyl-decorated prodiginines, which are of particular interest in this study due to a previously described particularly good plant compatibility and low toxicity, are not as readily accessible. In the present study, a new effective hybrid synthetic route was established. This included the engineering of a novel P. putida strain to provide enhanced levels of a bipyrrole precursor and an optimization of mutasynthesis, i.e. the conversion of chemically synthesized and supplemented monopyrroles to tripyrrolic compounds. Subsequent semisynthesis provided the hydroxylated prodiginine. The prodiginines caused reduced infectiousness of H. schachtii for Arabidopsis thaliana plants resulting from impaired motility and stylet thrusting, providing the first insights on the mode of action in this context. Furthermore, the combined application with rhamnolipids was assessed for the first time and found to be more effective against nematode parasitism than the individual compounds. To obtain, for instance, 50% nematode control, it was sufficient to apply 7.8 µM hydroxylated prodiginine together with 0.7 µg/mL (~1.1 µM) di-rhamnolipids, which corresponded to ca. ¼ of the individual EC50 values. In summary, a hybrid synthetic route toward a hydroxylated prodiginine was established and its effects and combinatorial activity with rhamnolipids on plant-parasitic nematode H. schachtii are presented, demonstrating potential application as antinematodal agents.